Penegakan Hukum Terhadap Pihak Pengelola Limbah Bahan Berbahaya Dan Beracun (B3) Rumah Sakit Yang Menimbulkan Pencemaran Lingkungan - Isma Isyana; Rafqi Rafshanjani Dalimunthe; Irwan Triadi (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Hospitals as one of the health service providers cannot be separated from the lives of people who always want to maintain their health. Every hospital must maintain cleanliness because it is a place used as a health facility. Hospital is a type of health service business to the community which certainly produces a lot of waste including hazardous waste in its operational activities. Just like settlements, hospitals also produce a lot of waste and perhaps more. It is difficult to manage B3 waste on their own, so not a few hospitals use B3 waste management services to other parties who of course still have to have a permit from the relevant agency to be able to manage B3 waste. Third parties in managing hospital B3 waste still have responsibilities to the hospital. Government efforts in providing environmental protection and management, and preventing environmental pollution are by providing administrative sanctions, criminal sanctions, civil sanctions. With the sanctions given to people or parties who commit environmental pollution, it is hoped that it can provide a deterrent effect to be better and wiser in managing the waste from their activities in order to preserve the environment and free the environment from pollution.